Implementation of the At-Tibyan (Tahajji) Method in Improving Al-Quran Recitation in Kindergarten - Syelvia Wulandari; Noor Baiti; Herman Taufik (EDUJAVARE: International Journal of Educational Research, 2025)
Early Humans are born without knowledge but are endowed with innate potential (fitrah) that enables development through the process of education. The Qur'an is the primary guideline in the life of Muslims; therefore, the ability to read the Qur'an needs to be introduced from an early age. A common problem found is children's inability to pronounce hijaiyah letters correctly. This study aims to describe the implementation of the tahajji method using the At-Tibyan book in improving Qur'anic reading (qira’ah) skills of early childhood students at TK TAUD SaQu Ar-Raudah, Marabahan District. This research employed a qualitative approach with a field research design. Data were collected through observation, interviews, and documentation, then analyzed descriptively. The results indicate that the implementation of the At-Tibyan method improves children's ability to read the Qur'an, particularly in recognizing hijaiyah letters and improving pronunciation accuracy. In addition, this method increases students' learning interest and assists teachers in delivering learning materials effectively. Therefore, the At-Tibyan method is considered effective for teaching Qur'anic reading to early childhood learners.